Exploring the TQM best practices in Malaysia hotel industry using Multi-Criteria Decision Making (MCDM) approach: A conceptual analysis - Sin, Kit Yeng; Muhammad Shahar, Jusoh; Noormaizatul Akmar, Ishak; Muhammad Zaini, Ahmad (AIP Publishing, 2016)
Quality has become a fundamental issue for organizational success in today’s dynamic business environment particularly hotel industry as it affects the stakeholders which involve government, employers, employees as well as the end users. Total Quality Management (TQM) has seen as a revolution in management whereby it not only began to exert its vigorous effect on national business system but also referred as an comprehensive approach for total organizational performance improvement. TQM literature has been widely addressed and many researchers evaluated the gaps in TQM to achieve organizational performance. However, the literature does not seem to agree on a universal framework for the implementation of TQM philosophy in hotel settings. This paper emphasizes the importance level of inter-dependency among the TQM which has rarely been explored in the preceding studies. A novel hybrid Multi-Criteria Decision Making (MCDM) model is used to address the dependence relationships of factors with the aid of grey relational analysis, Analytical Network Process (ANP) and Decision-Making Trial and Evaluation Laboratory (DEMATEL). The initial model of the study is designed by considering main criteria and sub-criteria of TQM using interview method. DEMATEL is employed to construct interrelations among criteria and sub-criteria in the integrated model. By using this approach, the inter-dependencies strength among the criteria and sub-criteria is tested. The ANP method is then applied in order to determine the relative importance of the TQM and used to identify how TQM are weighted and prioritized by the management representatives (MR) or hotel top management. The development of this MCDM model will assist Malaysia hotels in identifying the key elements and factors that need to be thoroughly considered and managed for achieving competitive advantage as well as be a guide for hotel entities to invent new quality management practices or improve existing management policies.